Women's Sexual Empowerment and Its Relationship to Contraceptive Use in Bangladesh: Findings From a Recent National Survey - Nishi Khatun; Sihab Howlader; Md. Mosfequr Rahman (Frontiers Media S.A., 2023)
Objectives: This study aimed to assess the relationship between women's sexual empowerment and contraceptive use among married Bangladeshi women from a nationally representative sample.Methods: Secondary data analysis was conducted using the Bangladesh Demographic and Health Survey (BDHS) 2017-18. The investigation covered a total of 14,515 married, non-pregnant women who were residing with their spouses. Multivariable logistic regression analysis was fitted to assess the relationship between the variables of interest.Results: A unit increase in the sexual empowerment scale increases the odds of contraceptive use by 13%. While increasing age, being Muslim, having a spouse who is older by more than 10 years, and living in rural areas are associated with lower odds of using contraceptives than their respective counterparts, secondary or higher levels of education, having more living children, exposure to TV or radio, and employment are associated with higher odds of using contraceptives.Conclusion: The study's findings point to the need for addressing women's perceptions of their right to sexual and reproductive health and equity in order to further efforts to achieve universal access to reproductive health services.